Does money buy happiness? Evidence from an unconditional cash transfer in Zambia - Luisa Natali; Sudhanshu Handa; Amber Peterman; David Seidenfeld; Gelson Tembo (Elsevier, 2018)
The relationship between happiness and income has been at the center of a vibrant debate, with both intrinsic and instrumental importance, as emotional states are an important determinant of health and social behavior. We investigate whether a government-run unconditional cash transfer paid directly to women in poor households had an impact on self-reported happiness. The evaluation was designed as a cluster-randomized controlled trial in rural Zambia across 90 communities. The program led to a 7.5 to 10 percentage point impact on women's happiness after 36- and 48-months, respectively (or 0.19-0.25 standard deviations over the control group mean). In addition, women have higher overall satisfaction regarding their young children's well-being, including indicators of satisfaction with their children's health and positive outlook on their children's future. Complementary analysis suggests that self-assessed relative poverty (as measured by comparison to other households in the community) is a more important mediator of program effects on happiness than absolute poverty (as measured by household consumption expenditures). Although typically not the focus of such evaluations, impacts on psychosocial indicators, including happiness, should not be discounted as important outcomes, as they capture different, non-material, holistic aspects of an individual's overall level of well-being. Keywords: Happiness, Subjective well-being, Income, Cash transfers, Zambia